EFFECT OF METHANOL CONCENTRATION AS A SOLVENT ON TOTAL PHENOLIC AND FLAVONOID CONTENT OF BELUNTAS LEAF EXTRACT (Pulchea indica L.) - Mahasuari, Ni Putu Sinta; Paramita, N. L. P. Vidya; Yadnya Putra, A.A Gede Rai (Journal Pharmaceutical Science and Application; Vol 2 No 2 (2020): Journal Pharmaceutical Science and Application, 2020)
Background: Beluntas (Pluchea indica L.) is an Indonesian plant that grows wild and is used as traditional medicine. Beluntas leaves are reported to contain phenolic, and flavonoid is a part of phenolic compounds. Phenolic compounds other than flavonoids include 1,3,4,5-tetra-O-caffeoylquinic acid, 3,4,5-tri-O-caffeoylquinic acid, chlorogenic acid, and ferulic acid. Flavonoid compounds in beluntas leaves are quercetin, apigenin, luteolin and chrysoeriol. Methanol solvents are reported to be able to extract higher polyphenol and flavonoid contents than other solvents. Objective: The purpose of this study is to determine the effect of 20%, 50% and 75% solvent concentration of methanol on total phenol and total flavonoid levels of beluntas leaf extract. Methods: In this study, the extraction process was carried out by maceration, the determination of total phenol content was carried out by the Follin-Ciocalteu method. Determination of total flavonoid levels was carried out by the Colorimetric method. Data on phenol and flavonoid levels were analyzed statistically. Results: The yield of beluntas leaf extract in this study was respectively from the lowest methanol concentration of 24.094% w/w, 31.126% w/w, 24.838% w/w. The value of total phenol levels increased with increasing methanol concentration, namely 124.84 mg GAE/g, 138.3 mg GAE/g, and 147.91 mg GAE/g. The highest total flavonoid value in 75% methanol extract is 69.72 mg QE/g, followed by 20% methanol extract at 46.29 mg QE/g and the lowest is found in 50% methanol extract at 32.80 mg QE/g. The results of statistical analysis using the Kruskal-Wallis test showed that there were significant differences (p<0.05) in the value of total phenol levels and total flavonoids of the three extracts. Conclusion: The difference in the concentration of methanol solvents affects the value of total phenol levels and total flavonoids with the highest value produced by a 75% methanol solvent. Keywords: Beluntas Leaves (Pluchea indica L.), Total Phenol Content, Total Flavonoid Content, Gallic Acid, Quercetin.